(untitled) (Research, Society and Development, 2024)
Introduction: Immunoglobulin A nephropathy (IgAN) predominantly affects children and young adults, with clinical presentation influenced by factors such as ethnicity and age. Currently, there are no reliable serum or urinary biomarkers for diagnosing IgAN, nor is there a specific treatment for the condition. Therefore, this study aims to explore aspects of renal disease to address current knowledge gaps. Methodology: This is an integrative review on IgAN. Data were gathered from the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), and the National Library of Medicine (PubMed), using the intersection of the keywords "IgA nephropathy," "renal disease," "biomarkers," "biopsy," and "clinical manifestations" to address the question formulated through the PICO strategy. Results and Discussion: The epidemiology of IgAN is poorly understood, but it is known to be more prevalent in males, children, and young adults. The pathogenesis involves the production of anomalous IgA following triggers such as infections or vigorous exercise, which are targeted by autoantibodies forming immune complexes deposited in the renal glomeruli. This leads to histological changes that manifest in various clinical presentations, primarily visible hematuria. Definitive diagnosis requires biopsy, and prognosis depends primarily on the degree of proteinuria and remaining renal function. Current treatment involves supportive measures for blood pressure and proteinuria control, with immunosuppression considered for severe cases. Conclusion: There are still controversies regarding the pathology and treatment of IgAN. Thus, further studies are needed to clarify optimal clinical management and risk factors for the condition.